(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The teaching landscape is rapidly changing, the technological rise of the 21stcentury and widespread integration of those technologies into our society, combined with access to the internet has integrally changed teaching in just a few years . Educational technology implies a behavioural science approach to teaching and learning in that it makes use of pertinent scientific and technological methods and concepts developed in psychology, sociology, communications, linguistics and other related fields. It also attempts to incorporate the management principles of cost effectiveness and the effic ient deployment and use of available resources in men and materials. Educational technology as a concept does not necessarily imply the use of machines and other items of hardware. Experience has shown that more often than not they involve such media, equipment and resources. The purpose of the present study was to find out whether there was any significant difference between educators of teacher education program with regard to gender, subject taught and age in their TPACK and its dimensions and also to find out there was any significant influence of educators of teacher education program teaching experience in their TPACK and its dimensions. TPACK questionnaire were used for collecting the required data from the population. The major findings revealed that there was no significant influence of educators of teacher education program teaching experience in their TPACK and its dimensions.